Boron Fertilization of Irrigated Alfalfa in Montana. Issue 1 (14th June 2018) - Sapkota, Anish; Meccage, Emily C.; Stougaard, Robert N.; Tanner, John P.; Peterson, Danielle M.; Torrion, Jessica A.
Abstract : Core Ideas: Boron (B) application increased petiole B in irrigated alfalfa but did not impact yield and quality. Low initial soil B is not a reliable measure of the need to amend with B using foliar application of irrigated alfalfa in Montana. Diagnosing signs of B deficiency coupled with in‐season petiole B analysis may be of better value to the producers. A boron (B) deficient soil may negatively impact irrigated alfalfa ( Medicago sativa L.) plant tissue sufficiency, thereby compromising yield and quality in a short‐season environment such as Montana. The objective was to determine the impacts of B fertilization on irrigated alfalfa yield and quality in 2015 and 2016 at Creston and Dillon, MT on fine sandy loam and silt loam soils, respectively. The initial soil B levels at the Creston and Dillon sites were 0.2 and 0.8 ppm, respectively. The study was conducted as a randomized complete block design with five B levels: (1) 0; split applications of (2) 0.50, (3) 1.00, (4) 2.00; and a one‐time application of (5) 2.00 lb/ac in four replications. Full doses of Treatment 5 and half the dose of Treatments 2–4 were applied in early spring at a 3‐inch regrowth height. The other half dosage of Treatments 2–4 was re‐applied at a 3‐inch plant height after the first cutting. A liquid 10% B AgriSolutions was foliar‐applied as B fertilizer. All the cuttings were performed at 10% bloom. Application of B increased ( P < 0.05) plant B concentration at both locations. Boron fertilization increased ( P < 0.05) crop yield for the second cutting in 2015 at Dillon but did not influence all of the other seasonal cuttings nor total yields for either year or location. No significant effect of B on forage quality was observed. This research suggests foliar B fertilization based on a low B soil test is not beneficial for irrigated alfalfa producers in Montana.